ROLE OF PHARMACIST IN COUNSELING ASTHMA TO IMPROVE PATIENT ADHERENCE IN YOGYAKARTA - Sari, Chynthia Pradiftha; Hakim, Lukman; I. DEWA PUTU P (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To identify the effect of pharmacist-provided counseling on patient adherence and to examine the correlation between adherence level and asthma therapy outcome Methods: Quasi-experimental through control-group design with pretest-posttest. Study was conducted during February–June 2013 (N=120). Only the intervention group received pharmacist counseling. All participants completed MMAS and ACT questionnaires before and after counseling. They were 18–60 y old and having<8 MMAS pretest score with moderate-severe persistent asthma. Results: The intervention was pharmacist counseling for 56 patients, and control group had 50 patients. After counseling, 3.92% severe persistent asthma patients showed low-medium adherence, and 62.64% moderate persistent asthma patients had medium-high adherence. The change of MMAS score in the intervention group was 3.71 and 2, and 1.23 and 1.64 in the control group. Wilcoxon and Mann Whitney test indicated a significant difference in patient adherence before and after counseling (p<0.001). Adherence was positively and significantly correlated with therapy outcome (p<0.001; r=0.583). Conclusion: Pharmacist counseling affects asthma patient adherence. There is a significant correlation between adherence and therapy outcome.